Country of Origin and Brand Image on Purchase Decision of South Korean Cosmetic Etude House - Elvina Marsha Devita; M.Y. Dwi Hayu Agustini (Journal of Management and Business Environment (JMBE), 2019)
This research aims at knowing the influence of country of origin (COO) and brand image on purchase decision of Etude House, a South Korean cosmetic brand. A sample of 100 consumers of Etude House was the respondents that were selected using snowball method. The questionnaire were distributed to women consumers who live in Semarang and have been using the products in the last three months. Multiple regression analysis was to see if the influence of COO and brand image on purchase decision is significant. The results show that COO and brand image had positive and significant influence on the purchase decision of Etude House products